If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 + X = 120 Solving 70 + X = 120 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + X = 120 + -70 Combine like terms: 70 + -70 = 0 0 + X = 120 + -70 X = 120 + -70 Combine like terms: 120 + -70 = 50 X = 50 Simplifying X = 50
| 8m-(9+6m)= | | -51=-8x+5 | | 3y-6=3(y-2)-1 | | X^2+3x+2.25=8.25 | | 5y-17=2y-3 | | 9*3/5=8/11w | | .7x-5.2=.4 | | -3(-3p-3)+12p=-(4p-9) | | 8y+3x=18 | | 72(x-2)=18(x+1) | | 20x-6=154 | | -4-7x=-53 | | ln(x+4)=5 | | p-1+p-17=4p-9-p | | 30+80=X | | 6(x-8)=4x-48+2x | | -8y+1=5 | | -5=7-4x | | (6x^2)*(6x^7)=(6x^2)*(6x^7) | | (6x^2)*(6x^7)=y | | 8(2-z)=-7z | | 11x-13=42 | | 36+8r=4(-1-8r) | | -p+7p-13=4p-1 | | (5-x)(2x-3)=0 | | X+20=120 | | 36-6z=-z | | (6x^2)*(6x^7)= | | 36-6z=-6z | | 8(y-3)=48 | | 90+90+(2x+4)+3x-29=360 | | 3t+5-2t=3-4t-2 |